Building Bridges with Words: Teacher–Student Talk Dynamics in Young Learners’ English Classrooms - Budiman, Jeihn N. C.; Ganap, Nindy N. (Journal of English Language Teaching, Literature and Culture, 2025)
Understanding effective teaching strategies alongside student needs plays a crucial role in selecting materials that align with students’ preferred learning styles. When teaching English to young learners, age is a significant factor, as early childhood is considered a critical period for language acquisition. During this golden age, the collaborative efforts of parents and teachers can enhance students' cognitive development, leading to better learning outcomes. This study utilized a literature review method, drawing from various previous research studies. The analysis followed several steps, starting from identifying the problem to interpreting the data. Classroom interaction emerged as a key component of the learning process, where both teachers and students are expected to actively participate. The findings reveal a noticeable imbalance between teacher talk and student talk, as supported by prior research. This imbalance highlights an important issue that educators need to address to foster a more engaging and participatory learning environment for students.